Apoptosis in the immune system - Krammer, Peter (Henry Stewart Talks, 2007)
Basics of apoptosis, Signalling through death receptors, Apoptosis in the immune system, Apoptosis in diseases: sepsis, stroke and spinal cord injury, Apoptosis and killer T cells, Apoptosis and p53, Apoptosis and cancer